Economic Analysis Child Labor Based Households in Bengkulu City - Rospida, Lela; Kamaludin, Kamaludin; Ridwan, Mochamad (International Journal of Economics and Financial Issues, 2021)
The purpose of this study was to analyze the influence of father characteristics, mother characteristics, household characteristics, child labor characteristics, and community, on work time of child labor in Bengkulu City. This research uses primary data. Sampling was done by incidental method. Data collected through interviews and questionnaires. The analytical method uses PLS-PM (Partial Least Square-Path Modeling). The results showed that the variables of father characteristics, mother characteristics, household characteristics and community had a negative and significant effect on the working hours of child labor. While the variable child labor characteristics had a positive and significant influence on working hours of child labor. If the father characteristics, the mother characteristics, the household characteristics, and the community are getting better, then the working hours for child labor will be reduced. While, if the child labor characteristics are getting better (the more it fits the criteria, namely male sex, the lower the education, and not going to school), then the work time of child labor will increase. The indicators on the father characteristic variables, that most determine are father's income and father's education. Indicators on the mother characteristics that most determine are mother's income, mother's education and mother's occupational status. The most determine indicators of household characteristics are household assets, number of family members, number of children, number of working family members, and parents' income. Indicators on the most determine characteristics of child labor are the gender of child labor, the education of child labor and the status of child labor. The most determine indicators in the community are market availability and school availability. Keywords: Child labor, Household, Working Hours, Indonesia, Bengkulu JEL Classifications: J01, J13 DOI: https://doi.org/10.32479/ijefi.9827